Everlast : a graphic novel - Murray, Chad Michael; Christy, Stephen; Dove, Sean; Hairsine, Trevor; Huerta, Andrew; Lanphear, Dave (USA : c)
"A pre-apocalyptic tale, Everlast follows Derek Everlast, a man whose destiny in life is guiding others to a place of rebirth for mankind called Haven. Following an instinct called the Nudge, bestowed on him by a higher power, Derek is guided to the next chosen human destined to survive, a little girl named Melissa. In a harrowing adventure, he must deliver her safely to Haven before the End of Days. Everlast tells a story of choice, love, friendship, and, most of all, survival. Will you be chosen?"
700-799
Keywords: End of the world -- Comic, books, strips, etc. -- Fiction; Graphic novels; Fantasy comic books, strips, etc